نظام التحكم الكلي في حمل التدفئة، المبني على أساس طريقة التصميم الرياضي - محمد زهرة (Tishreen University, 2019)
منذ سنوات طويلة يجري العمل على إنشاء أنظمة جديدة للتحكم الآلي في أحمال التدفئة، وإدخالها في المحطات الفرعية لنظام التدفئة على أساس معادلات التصميم لنظام التحكم. إن تطبيق هذا التصميم يتم بطريقة المعلوماتية لتقييم نظام التدفئة في الأبنية المدفأة، والذي يعتبر واحداً من أهم الاتجاهات المستقبلية لأتمتة أحمال التدفئة لأنظمة التدفئة المركزية الحديثة باستخدام تقنية الدارات المتكاملة الدقيقة وفقاً للمعادلات الرياضية لنظام التحكم المصمّم، والذي يعطي توفيراً ملحوظاً في الحرارة السنوية اللازمة للتدفئة، الذي يؤدي بدوره إلى توفير اقتصادي في طاقة الوقود اللازمة للتدفئة. وكذلك المحافظة على درجة الحرارة في الأبنية المدفئة بحدود (20-22 ْم )عن طريق التوزيع المنتظم لحرارة التدفئة بما يتناسب مع الضياعات الحرارية الفعلية للأبنية. ويؤمن استقراراً في استهلاك مياه الشبكة لا يسمح بزيادته عند الاستهلاك الأعظمي.   Work has been going on for years to build up new system for Automatic control of heating loads, and using these systems in the sub -total- heating- station, on the basis of a designed equation of the control system. Applying this design by the informatics method for evaluation of the heating system in the building. This is one of the most important future requirements for heating loads automization of the new central -heating  systems, using the new I.C. techniques according to the proposed equation of the designed control  system, this system apparently save the yearly required heating and refrigeration. Which in turn leads to an economical saving in the required amount of fuel used for heating. This also keeps the amount of buildings- temperature between (20- 22 co), by thermal heating balance distribution, according to the actual heating loss of the building, It also makes consuming stabilization in the water -net, and prevents any increase at peak times